Autoimmune disorders in patients with idiopathic thrombotic thrombocytopenic purpura - John, M.-L.; Scharrer, I. (Hämostaseologie, 2012)
76 German patients suffering from thrombotic thrombocytopenic purpura (TTP) were interrogated about the prevalence of cooccurring autoimmune disorders. In order to analyze a possible association of TTP with the questioned diseases, a comparison of prevalence rates between the patient group and the general population has been made for each disease. Results: Compared to the estimated prevalence rates, the statistical analysis revealed an unexpected high occurrence of the following disorders within the patient group: Hashimoto’s thyroiditis (23.5% within the patients compared to 0.7% within the general population, p<0.001), systemic lupus erythematosus (SLE) (6.5% in patients to 0.025% in the general population, p<0.001), immune thrombocytopenic purpura (ITP) (6.3% in patients to 0.02% in the general population, p < 0.001), psoriasis (9.4% in patients to 2.5% in the general population, p = 0.005) and celiac disease (3.1% in patients to 0.2% in the general population, p = 0.007). Conclusion: These findings confirm the mentioned tendency of autoimmune diseases to co-occur in one individual and argue once more for a genetic susceptibility in idiopathic TTP as well as in autoimmune disorders.
Keywords: TTP; autoimmunity; genetic susceptibility; HLA